The prevalence and effects of stalking: a replication study - Dreßing, Harald; Gass, Peter; Schultz, Katharina; Kühner, Christine (Deutsches Ärzteblatt, 2020)
Background: In 2003, we carried out the first epidemiological study on the frequency and effects of stalking in Germany that was based on a random population sample. We repeated the study with the same design in 2018 in order to assess any potential alterations over time in the frequency of stalking and of psychological problems in the affected persons. As far as we know, this is the first replication study of this kind to be carried out anywhere. - Methods: 1000 women and 1000 men were randomly chosen from the residents' registration data of Mannheim, Germany. Each one of them received, by mail, a comprehensive questionnaire about stalking, as well as the WHO-5 Well-Being Index and the German version of the Patient Health Questionnaire (PHQ-D). - Results: In the Mannheim population samples (2003: N = 675; 2018: N = 444), the lifetime prevalence of being stalked was 11.6% in 2003 (95% confidence interval, [9.2; 14.4]) and 10.8% in 2018 [8.1; 13.7]. In both 2003 and 2018, persons who had been stalked had significantly worse mental well-being than unaffected persons (WHO-5 summated score 2003: 11.2 [9.7; 12.6] vs. 15.5 [15.1; 16.0], WHO-5 summated score 2018: 11.8 [10.1; 13.6] vs. 14.5 [13.9; 15.0]). A markedly higher percentage of persons who had been stalked also fulfilled the syndrome criteria for at least one mental disorder (PHQ-D 2003: 50.0% vs. 22.5%; odds ratio [OR]: 3.5 [2.1; 5.6], PHQ-D 2018: 46.5% vs. 24.4%; OR: 2.7 [1.4; 5.1]). In 2018, as in 2003, persons who had been stalked were dissatisfied with, or unaware of, the opportu - nities that they had to get help from the police and the judicial system. - Conclusion: Stalking remains a major problem that must be taken seriously. Physicians and psychologists should be well informed about it in order to help affected persons who turn to them for medical and psychological assistance.
DOI funktioniert nicht
Gesehen am 06.08.2020